PENGARUH MINAT DAN PERILAKU BELAJAR TERHADAP HASIL BELAJAR AKUNTANSI KEUANGAN MENENGAH I MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Wahyu Ramadhani Saputra; Gimin Gimin; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted at the Economic Education FKIP, University of Riau with the aim of knowing the effect of interest in learning and learning behavior on learning outcomes of secondary financial accounting for students of economic education, University of Riau. The population in this study were 123 students from the 2016, 2017, 2018 class and the sampling technique in this study used a simple random sampling technique with the Slovin formula which resulted in 94 samples. The data collection technique is done through a questionnaire technique, while the types and sources of data are primary data and secondary data. Furthermore, the data were analyzed using multiple regression analysis, simultaneous regression coefficient test (F test), partial correlation test, and determination coefficient (R2). The results showed that the variables of interest in learning and learning behavior simultaneously affect learning outcomes. This means that the independent variables jointly affect the dependent variable. Furthermore, based on the partial correlation test, it can be seen that the variable interest in learning affects learning outcomes indicated by a significance of 0.015 while for learning behavior variables influencing learning outcomes is indicated by a significance of 0.030. With the coefficient of determination of 0.153. This means that the contribution of the influence of the independent variable to the dependent variable is 15.3%. While the remaining 84.7% is determined by other variables. Based on the research results, suggestions or recommendations from researchers are that students should be able to increase their interest in learning and learning behavior properly so that learning outcomes can be achieved properly. Key Words: Interest in Learning, Learning Behavior, Learning Outcomes